PROMISING DIAGNSOTIC MARKER AT NICU AND PICU-NEW APPROACHES FOR DIAGNOSTIC AND TREATMENT - Aspazija Sofijanova; Silvana Naunova Timovska; Mica Kimovska-Hristova; Tamara Voinovska; Hristina Mangjukovska-Bicevska; Spasija Neskova; Olivera Jordanova; Sonja Bojadjieva; Ilija Kirovski (Macedonian Association of Anatomists, 2019)
The aim of this study is evaluate the initial PCT levels on the outcome of patients in pediatric intensive care units and find out if these biomarker can be used to predict sepsis. The study was designed as a prospective, clinical, investigation conducted in the period sixth months, which included 45 (M:F=25:20) newborns with two or three clinical signs of sepsis hospitalized in the Intensive Care Unit at the PHI University Clinic for Children Diseases. The patient have been divided into two groups: I group included 31 septic newborns with negative blood culture and II group - 14 septic newborns with positive blood cultures. Results of blood count (WBC), CRP and PCT, were recorded. Procalcitonin PCT levels at first 24 hours of the admission were increased in all 45 newborns (≥2 ng/mL). The values of C-reactive protein gradually increase after 12-36 hours at admission. The second measurement, after 3 days usage of an adequate antibiotic treatment, the levels of PCT is decreased,regardless of whether blood culture is positive or negative, except 5 patients develop severe sepsis, and three patients develop septic shock. After the third measurement the levels of PCT and CRP is decreased. NIV was used in 39.8% patients and Invasive MV was used in 29.8% patients.Sensitivity of procalcitonin 83.5%, Specificity of procalcitonin 81.3%. Procalcitonin value is a early prognostic factor for sepsis and it is a reliable parameter whether an appropriate antibiotic for the treatment is used,thus increasing newborns safety,and reducing costs .
Keywords: sepsis; C-reactive protein; procalcitonin PCT